Efficacy of pudendal nerve block for alleviation of catheter-related bladder discomfort in male patients undergoing lower urinary tract surgeries: A randomized, controlled, double-blind trial. Issue 49 (December 2017) - Xiaoqiang, Li; Xuerong, Zhang; Juan, Liu; Mathew, Bechu Shelley; Xiaorong, Yin; Qin, Wan; Lili, Luo; Yingying, Zhu; Jun, Luo
Abstract: Background: Catheter-related bladder discomfort (CRBD) to an indwelling urinary catheter is defined as a painful urethral discomfort, resistant to conventional opioid therapy, decreasing the quality of postoperative recovery. According to anatomy, the branches of sacral somatic nerves form the afferent nerves of the urethra and bladder triangle, which deriving from the ventral rami of the second to fourth sacral spinal nerves, innervating the urethral muscles and sphincter of the perineum and pelvic floor; as well as providing sensation to the penis and clitoris in males and females, which including the urethra and bladder triangle. Based on this theoretical knowledge, we formed a hypothesis that CRBD could be prevented by pudendal nerve block. Objective: To evaluate if bilateral nerve stimulator-guided pudendal nerve block could relieve CRBD through urethra discomfort alleviation. Design and Setting: Single-center randomized parallel controlled, double blind trial conducted at West China Hospital, Sichuan University, China. Participants: One hundred and eighty 2 male adult patients under general anesthesia undergoing elective trans-urethral resection of prostate (TURP) or trans-urethral resection of bladder tumor (TURBT). Around 4 out of 182 were excluded, 178 patients were randomly allocated into pudendal and control groups, using computer-generated randomized numbers in a sealed envelope method. A total of 175 patients completed the study. Intervention: Pudendal group received general anesthesia along with nerve-stimulator-guided bilateral pudendal nerve block and control group received general anesthesia only. Main outcome measures: Incidence and severity of CRBD; and postoperative VAS score of pain. Results: CRBD incidences were significantly lower in pudendal group at 30 minutes (63% vs 82%, P  = .004), 2 hours (64% vs 90%, P <  .000), 8 hours (58% vs 79%, P  = .003) and 12 hours (52% vs 69%, P  = .028) also significantly lower incidence of moderate to severe CRBD in pudendal group at 30 minutes (29% vs 57%, P <  .001), 2 hours (22% vs 55%, P <  .000), 8 hours (8% vs 27%, P  = .001) and 12 hours (6% vs 16%, P  = .035) postoperatively. The postoperative pain score in pudendal group was lower at 30 minutes ( P  = .003), 2 hours ( P <  .001), 8 hours ( P <  .001), and 12 hours ( P <  .001), with lower heart rate and mean blood pressure. One patient complained about weakness in levator ani muscle. Conclusion: General anesthesia along with bilateral pudendal nerve block decreased the incidence and severity of CRBD for the first 12 hours postoperatively.